Dynamical Signatures of Ground‐State Degeneracy to Discriminate against Andreev Levels in a Majorana Fusion Experiment. Issue 1 (19th November 2019) - Grabsch, A.; Cheipesh, Y.; Beenakker, C. W. J.
Abstract: Detection of the fusion rule of Majora na zero‐modes is a near‐term milestone on the road to topological quantum computation. An obstacle is that the non‐deterministic fusion outcome of topological zero‐modes can be mimicked by the merging of non‐topological Andreev levels. To distinguish these two scenarios, the dynamical signatures of the ground‐state degeneracy that is the defining property of non‐Abelian anyons is searched for. By adiabatically traversing parameter space along two different pathways, one can identify ground‐state degeneracies from the breakdown of adiabaticity. It is shown that the approach can discriminate against accidental degeneracies of Andreev levels. Abstract : A demonstration of the fusion rule of Majorana zero‐modes would be a milestone in the development of a topological quantum computer. An obstacle is that the non‐deterministic fusion outcome can be mimicked by trivial Andreev levels. Here, it is shown that one can distinguish these by adiabatically traversing parameter space along two different pathways of coupling and decoupling operations.